DELIBERATIVE THINKING AND ITS ROLE IN ENHANCING THE CHARACTERISTICS OF ENTREPRENEURIAL WORK-A SURVEY STUDY OF THE OPINIONS OF A SAMPLE OF TEACHERS IN PRIVATE SCHOOLS IN NAJAF GOVERNORATE - Thawra Abed Kareem (Scholars Digest Publishing, 2025)
This research aims to investigate the nature of the relationship between managerial thinking and the characteristics of entrepreneurial work in a number of private schools in Najaf Governorate. The importance of the current research is determined by the scarcity of studies that tried to determine and know the nature of the relationship between its variables (managerial thinking and the characteristics of entrepreneurial work), as well as the attempt of the current research to address a realistic problem that directly affects the educational reality in Najaf Governorate, as the research community (125), and relied on the method of the purposive sample, which are the founders (shareholders) in private schools and their number (85) with a response rate of (68%) of the total community, and analyzed by the statistical program SPSS v20. The results showed that there is a knowledge gap to explain the nature of the relationship between the variables of prudential thinking and the characteristics of the entrepreneurial work in the organizations studied, and there is a direct impact relationship between (prudential thinking and the characteristics of the entrepreneurial work).
Keywords: Thought Management, Characteristics of Entrepreneurial Work, Private Schools.